A History of the "Festival of the Arts" at Southwest Virginia Community College (1995–2018): Community Service through Music. Issue 1 (October 2020) - Wallace, Elizabeth Mitchell
The purpose of this article is to describe the development, mission, and events of the Festival of the Arts at Southwest Virginia Community College (1995–2018) with special emphasis on community involvement and community enrichment. The festival serves as a tool in fulfilling the cultural enrichment mission and community service function of the college. Southwest Virginia Community College (SWCC) is a rural community college located in Richlands, VA, with a service area of more than 1, 800 square miles, and a service area population of approximately 107, 000 people. SWCC acts as the cultural center of its geographically broad service area, which is reflected in the mission of the college and is realized through initiatives such as the Festival of the Arts. After a regional performance by Pavlina Dokovska nearly a decade earlier, Dokovska became more involved in the arts community of Southwest Virginia, and she was instrumental in the official launch of the Festival of the Arts 1995. The Festival continued to evolve to an annual two-week event hosted by the college, bringing in nationally and internationally acclaimed artists for workshops, performances, and multicultural-centered education open to the public.